APLIKASI MEDIA PEMBELAJARAN INTERAKTIF SISTEM PANCA INDERA MANUSIA MENGGUNAKAN TEKNOLOGI AUGMENTED REALITY UNTUK SISWA SMP - Ihsanul Ulia, Rifa; Fajar Rodiansyah, Sandi (Universitas Majalengka, 2019)
Natural Sciences (IPA) is one of the subjects taught at the junior high school level. By using the lecture method, describing it on the board, or just looking at it in a textbook, it creates difficulties for most students in understanding the material. Factors causing difficulties in understanding students are due to the lack of visualization of real objects from the material presented. This raises a sense of laziness and saturation towards students in learning the five senses which is one of the sub-material found in junior high school science subjects. To overcome the problems mentioned above, the writer tries to compile a study entitled